Avaliação da aprendizagem de alunos com deficiência em cursos das ciências exatas: estudo de caso em uma Instituição Pública Federal de Ensino Superior na Cidade de Fortaleza-Ceará - Carvalho, Francisca Samara Teixeira (2013)
The specialized literature indicates a conceptual evolution concerning learning evaluation. Different from the exam, characteristic of the Traditional Pedagogy that was structured in 16th and 17th centuries, the concept of learning evaluation is an answer to a current demand, since the memorization and reproduction of information, by students, are not more necessary nowadays, when we need a procedural, critic and autonomous learning, related to the fast transformations of a society characterized by the easy access to information. The exam presents the following characteristics: it is punctual, qualifying, static, antidemocratic and authoritarian. It is harmful to any student, but it is worse to disabled students. Disabled students have legal rights to a specific evaluation, in agreement with their educational needs. Therefore, formative evaluation is considered the most appropriate model of learning evaluation at present for all students, especially for disabled students. In turn, the formative learning evaluation presents the following characteristics: it is procedural, diagnostic, dynamics, democratic, dialogued and inclusive overall. The main purpose of the current research is to accomplish an investigation about the practice of learning evaluation for disabled students registered in graduate and postgraduate level courses of Exact sciences in a Public Institute of Higher Education, in Fortaleza-Ceará. Specifically, this study aimed: i) knowing the difficulties lived by students, professors and coordinators regarding learning evaluation for disabled students; ii) identifying the accessibility conditions concerning the practices of learning evaluation; iii) gathering contributions of students, professors and coordinators for an inclusive practice of learning evaluation. Thus, a qualitative research was accomplished, as a case study. The semi-structured interview and the semi-structured questionnaire were used as instruments for data collection. A content analysis of the collected data was accomplished. The sample was composed by: 7 disabled students; 4 graduate level course’s coordinators and 7 professors; 18 subjects altogether. The results revealed a lack of an appropriate formation. Consequently, the professor do not know how to deal with disabled students and the traditional exam prevails. Suggestions were presented so that the professors of the institution were submitted to formation courses on the theme. It was also emphasized the need of an identification or an institutional registration of those students as an initial step of a better pedagogic service.